Book Review: Espaço, corpo do tempo. A construção geográfica da sociedade [Space, body of time. The geographical construction of society], by Ruy Moreira - Zanotelli, Claudio (Geografares, 2019)
Book Review: Espaço, corpo do tempo. A construção geográfica da sociedade [Space, body of time. The geographical construction of society], by Ruy Moreira. Originated from the doctoral thesis defended by the author in 1994 and published only in 2019, the book reviews six important authors from different periods of French Geography in its first chapters (Reclus, La Blache, Jan Brunhes, Max Sorre, Pierre George and Paul Claval ). As Ruy Moreira writes, the book is “... a journey to the classics, with the aim of searching for theory where it can be found in all senses…” aiming to extract what is the main part of their works and make a critical appraisal in the following chapters of the book.